Diverse new taxa of the enigmatic family Permotanyderidae (Insecta: Mecoptera), with notes on the phylogeny of Aneuretopsychina (long-proboscid scorpionflies) - Bashkuev, Alexey S. (Zootaxa, 2022)
Remarkable new finds of Permotanyderidae, an enigmatic “Diptera-like” mecopteran family hitherto known only from the Upper Permian of Australia, are described from the Upper Permian and transitional Permian–Triassic beds in Russia (northern European Russia, southern Urals, and the Tunguska and Kuznetsk Basins). The new taxa are Permotanyderus sibiricus sp. nov., P. sensibilis sp. nov., P. rakitovi sp. nov., Rudimentanus rieki gen. et sp. nov., R. cisuralicus sp. nov., Permotanyderites pseudopolycentropoides gen. et sp. nov., Chimaeropteron antiquum gen. et sp. nov. and Ch. agmatos sp. nov. The most archaic genus, Chimaeropteron gen. nov., is assigned to the new subfamily Chimaeropterinae. Choristotanyderus nanus Riek, 1953 is transferred to Permotanyderus Riek, 1953. The distinct suctorial mouthparts revealed in P. nanus and the analysis of wing characters provide evidence for the affinity of Permotanyderidae with the long-proboscid families Nedubroviidae and Pseudopolycentropodidae.